Parental Assistance during Online Learning: An Overview and Significance - Nur Heni; Nurbianta Nurbianta (Universitas Muhammadiyah Lampung, 2021)
Parents are the first to educate a child in a family. This is because family is the closest part of a person's life since childhood. Along with the pandemic that is spreading in Indonesia, the learning system that is implemented is online. The role of parents is needed in this learning process. So, this research was conducted to find out the level of enthusiasm and forms of mentoring the parents to their children during learning from home. This study uses the qualitative method. In the process of retrieving data, it is done by providing a questionnaire via google form containing 10 statements filled out by respondents of 20 people. Data from research that has been collected is then presented and then analyzed and drawn conclusions. The results of the study showed that the majority of parents of students are still enthusiastic about accompanying their children during the learning process carried out from home. The forms of assistance provided can be in the form of direct assistance during the learning process, as a substitute for teachers, and the provision of facilities that are needed during the learning process.